Assessment of Effectiveness of Health and Safety Systems in Construction Industry: A Case Study Lee Construction Ltd - Wanjiku, Josephine; Magali, Jeseph (Global Journal of Health Sciences, 2016)
Purpose: The general objective of the study was to assess the effectiveness of health and safety systems in construction industry and more specifically in Lee construction Ltd. Methodology: The study utilized qualitative, descriptive and quantitative research methodology to assess how employees of Lee construction Ltd experience the effectiveness of health and safety systems in their organization. The population of the study was 150 permanent and 200 casual employees of Lee Construction Ltd. The final sample size was 100 employees. In which case 40 were permanent and 60 were casual employees. This study used primary data which was collected through use of a questionnaire. SPSS was used to produce frequencies, descriptive and inferential statistics which was used to derive conclusions and generalizations regarding the study. Results: The study found out that knowledge has a positive influence on health outcome though not significant while management prioritization, attitude and practice have a positive and significant influence on health outcome. Unique contribution to theory, practice and policy: The study recommend that attention to the detail of regulatory frameworks may be necessary to ensure they meet the requirements of ILO Convention and properly support the activities of health and safety representatives.